An Efficient Face Recognition Using SIFT Descriptor in RGB-D Images - M. I. Ouloul; Z. Moutakki; K. Afdel; A. Amghar (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Automatic face recognition has known a very important evolution in the last decade, due to its huge usage in the security systems. The most of facial recognition approaches use 2D image, but the problem is that this type of image is very sensible to the illumination and lighting changes. Another approach uses the 3D camera and stereo cameras as well, but it’s rarely used because it requires a relatively long processing duration. A new approach rise in this field, which is based on RGB-D images produced by Kinect, this type of cameras cost less and it can be used in any environment and under any circumstances. In this work we propose a new algorithm that combines the RGB image with Depth map which is less sensible to illumination changes. We got a recognition rate of 96, 63% in rank 2.